Early Changes in Puffing Intensity When Exclusively Using Open-Label Very Low Nicotine Content Cigarettes. Issue 11 (7th May 2022) - White, Cassidy M; Watson, Clifford; Bravo Cardenas, Roberto; Ngac, Phuong; Valentin-Blasini, Liza; Blount, Benjamin C; Koopmeiners, Joseph S; Denlinger-Apte, Rachel L; Pacek, Lauren R; Benowitz, Neal L; Hatsukami, Dorothy K; Donny, Eric C; et al.
Abstract: Introduction: In response to reducing cigarette nicotine content, people who smoke could attempt to compensate by using more cigarettes or by puffing on individual cigarettes with greater intensity. Such behaviors may be especially likely under conditions where normal nicotine content (NNC) cigarettes are not readily accessible. The current within-subject, residential study investigated whether puffing intensity increased with very low nicotine content (VLNC) cigarette use, relative to NNC cigarette use, when no other nicotine products were available. Aims and Methods: Sixteen adults who smoke daily completed two four-night hotel stays in Charleston, South Carolina (United States) in 2018 during which only NNC or only VLNC cigarettes were accessible. We collected the filters from all smoked cigarettes and measured the deposited solanesol to estimate mouth-level nicotine delivery per cigarette. These estimates were averaged within and across participants, per each 24-h period. We then compared the ratio of participant-smoked VLNC and NNC cigarette mouth-level nicotine with the ratio yielded by cigarette smoking machines (when puffing intensity is constant). Results: Average mouth-level nicotine estimates from cigarettes smoked during the hotel stays indicate participants puffed VLNC cigarettes with greater intensity than NNC cigarettes in each respective 24-h period. However, this effect diminished over time ( p < .001). Specifically, VLNC puffing intensity was 40.0% (95% CI: 29.9, 53.0) greater than NNC puffing intensity in the first period, and 16.1% (95% CI: 6.9, 26.0) greater in the fourth period. Conclusion: Average puffing intensity per cigarette was elevated with exclusive VLNC cigarette use, but the extent of this effect declined across four days. Implications: In an environment where no other sources of nicotine are available, people who smoke daily may initially attempt to compensate for cigarette nicotine reduction by puffing on individual cigarettes with greater intensity. Ultimately, the compensatory behavior changes required to achieve usual nicotine intake from VLNC cigarettes are drastic and unrealistic. Accordingly, people are unlikely to sustain attempts to compensate for very low cigarette nicotine content.